Bile leak following T-tube removal - Gamal G Shemy; Ahmed M Hassan; Abd Al-Kareem Elias (Wolters Kluwer Medknow Publications, 2021)
Background and aim and objectives T-tube choledochostomy is performed following open or laparoscopic common bile duct exploration. There is increased concern regarding safety and efficiency of choledochostomy. The present paper evaluates the short-lived effectiveness and safety of T-tube bile leak after its removal. Patients and methods A total of 86 cases of choledocholithiasis were admitted to Al-Azhar University Hospital, Assiut. They underwent cholecystectomy (open), choledochotomy, and T-tube choledochostomy. T-tube choledochography was performed 10 days after surgery, and removal of the tube was done after 12 days. Results Morbidities, mainly bile leak and peritonitis, were estimated. A total of 10 patients had evidence of radiological leak. Marked biliary reactions were noticed in six cases promptly following T-tube removal. Five of these cases had clinical peritonitis, treated conservatively. Only one patient had biliary peritonitis and required reoperation. Conclusion The operative use of T-tube choledochostomy has been in dramatical decline in the past 20 years (owing to the development and adoption of removal lesser invasive maneuvers of choledocholithiasis removal). Manipulation of T-tube (situation and extraction) is technically exigent. Intricacy and morbidity are critical; thus, it is recommended not to be performed as a routine maneuver. Easier options must be taken into account initially.